(untitled) (JURNAL KEPERAWATAN, 2014)
Abstract: Patient Safety Goals is a requirement to be implemented in all hospitals accredited by the Commission on Accreditation of Hospitals. The use of patientâ€™s identification bracelet is the first implementation of the six targets Patient Safety Goals, that is the accuracy of the identification of patients that aims to be able to identify patients who were admitted to the hospital, appropriately, at the time of service or treatment. Purpose: to know the description of the patient knowledge about the installation of the patient identification bracelet in inpatient A BLU RSUP Prof. Dr. R. D. Kandou Manado. Methods: this study used a descriptive survey. The sampling technique used is total sampling of respondent with 90 patients. Results: the study showed that knowledge most of the patients shave lack knowledge about the definition (68.9%), lack about purpose (67.8%), good about the use (53.3%), and good about characteristics (61.1%). Conclusion: description of the patient knowledge about the installation of the patient identification bracelet includes definition, purpose, the use and charateristics in inpatient A BLU RSUP Prof. Dr. R. D. Kandou Manado is in either category. Suggestions: patient’s knowledge needs to be maintained so that properly maintained patient safety with the setting up of leaflets about identification bracelet will optimize patient safety policies that have been implemented in hospitals. Keywords: Patientâ€™s Knowledge, Identification Bracelet Abstrak: Sasaran Keselamatan Pasien (SKP) merupakan syarat untuk diterapkan di semua rumah sakit yang diakreditasi oleh Komisi Akreditasi Rumah Sakit (KARS). Penggunaan gelang identifikasi pasien adalah implementasi sasaran pertama dari 6 Sasaran Keselamatan Pasien yaitu ketepatan identifikasi pasien yang bertujuan untuk dapat mengidentifikasi pasien yang dirawat inap di rumah sakit secara tepat pada saat dilakukannya pelayanan maupun pengobatan. Tujuan penelitian: untuk mengetahui gambaran pengetahuan pasien tentang pemasangan gelang identifikasi pasien di instalasi rawat inap A BLU RSUP Prof. Dr. R. D. Kandou Manado. Desain penelitian: survey deskriptif. Teknik pengambilan sampel yang digunakan adalah total sampling dengan jumlah responden 90 pasien. Hasil penelitian: menunjukkan bahwa pengetahuan pasien sebagian besar kurang tentang pengertian (68,9%), kurang tentang tujuan (67,8%), baik tentang pemakaian (53,3%), dan baik tentang karakteristik (61,1%). Kesimpulan: gambaran pengetahuan pasien tentang pemasangan gelang identifikasi pasien meliputi pengertian, tujuan, pemakaian, dan karakteristik di Instalasi Rawat Inap A adalah dalam kategori baik. Saran: pengetahuan pasien perlu dipertahankan agar keselamatan pasien terjaga dengan baik dengan pemasangan leaflet tentang gelang identifikasi akan mengoptimalkan kebijakan keselamatan pasien yang telah diterapkan di rumah sakit. Kata Kunci: Pengetahuan Pasien, Gelang Identifikasi